Eudora Welty: Sensing the Particular, Revealing the Universal in Her Southern World - Pearl McHaney (Transatlantica)
Eudora Welty writes poetic prose that is painted with colors—red, rose, blue, green, silver, black, white, pearly gray, golden-yellow, rich in figurative language, and resplendent in sensory images and synaesthesia. Welty’s art illustrates an extraordinary sensitivity for discovering the South, in particular, but also the world at large. Examining how Welty’s observations lead to her senses of smell, touch, and sound in the stories “June Recital” and “Moon Lake,” selected letters and her comments on one of her photographs, and lastly, the stories “A Sketching Trip” and “The Demonstrators,” I argue that Welty pictures the invisible and writes the unsayable by her use of the senses with two results. First, she creates a sense of the South that is simultaneously particular and universal. To illustrate this, I analyze passages especially replete in visual and olfactory senses. Second, Welty’s sensory language gives meaning to the abstract, universal concepts such as joy, love, art, and fear.